The effects of leveraged buyouts on productivity and related aspects of firm behavior - Lichtenberg, Frank R.; Siegel, Donald (Journal of Financial Economics, 1990)
We investigate the effects of leveraged buyouts on total factor productivity (TFP) and related variables using a longitudinal database including over 12,000 manufacturing plants. LBOs (particularly MBOs) that occured during 1983–1986 had a strong positive effect on TFP in the first three post-buyout years: plant productivity increased from 2.0% above industry mean in the three pre-buyout years to 8.3% above industry mean in the three post-buyout years. However, 1981 and 1982 buyouts had no significant productivity effect. The employment and compensation of white-collar workers decline following buyouts, but those of blue-collar workers are unchanged.